2020
DOI: 10.3390/cancers12092530
|View full text |Cite
|
Sign up to set email alerts
|

pT1 Colorectal Cancer Detected in a Colorectal Cancer Mass Screening Program: Treatment and Factors Associated with Residual and Extraluminal Disease

Abstract: The aim of this study is to describe the treatment of pT1 colorectal cancer (CRC) in a mass screening program, the surgery-related complications and the factors associated with residual disease after endoscopic resection and extraluminal disease after surgery. We included in this retrospective analysis all the pT1 CRC detected in the Galician CRC screening program between May 2013 and June 2019. We determined which variables were independently associated with the outcomes of the study through a multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…In a recent study evaluating risk factors for an adverse prognosis after ER of T1 tumors, the variables related to surgical rescue were piecemeal resection (OR 4.48, 95 %CI 1.48–13.6), infiltrated/nonevaluable resection border (OR 7.44, 95 %CI 2.12–26.0), not well-differentiated histology (OR 4.76, 95 %CI 1.07–20.0), vascular infiltration (OR 8.24, 95 %CI 2.72–25.0), and Haggitt 4 infiltration of the submucosa (OR 5.68, 95 %CI 2.62–12.3). Residual disease after ER was associated with infiltrated/non-evaluable resection border (OR 34.9, 95 %CI 4.08–298), not well-differentiated histology (OR 6.67, 95 %CI 1.05–50.0), and vascular infiltration of the submucosa (OR 7.61, 95 %CI 1.55–37.4) 208 . So, clearly a positive vertical margin is a risk factor for residual disease and need for additional surgery and potential for LNM, as suggested by the study of Boenicke et al This showed that in patients who underwent ER of malignant polyps followed by surgery, even though 63 % of resection margins were positive (a free margin was not defined as a tumor-free extent of more than 1 mm), subsequent surgical specimens showed residual carcinoma in only 2.8 % but LNM in 7.6 % 209 .…”
Section: Management After Endoscopic Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study evaluating risk factors for an adverse prognosis after ER of T1 tumors, the variables related to surgical rescue were piecemeal resection (OR 4.48, 95 %CI 1.48–13.6), infiltrated/nonevaluable resection border (OR 7.44, 95 %CI 2.12–26.0), not well-differentiated histology (OR 4.76, 95 %CI 1.07–20.0), vascular infiltration (OR 8.24, 95 %CI 2.72–25.0), and Haggitt 4 infiltration of the submucosa (OR 5.68, 95 %CI 2.62–12.3). Residual disease after ER was associated with infiltrated/non-evaluable resection border (OR 34.9, 95 %CI 4.08–298), not well-differentiated histology (OR 6.67, 95 %CI 1.05–50.0), and vascular infiltration of the submucosa (OR 7.61, 95 %CI 1.55–37.4) 208 . So, clearly a positive vertical margin is a risk factor for residual disease and need for additional surgery and potential for LNM, as suggested by the study of Boenicke et al This showed that in patients who underwent ER of malignant polyps followed by surgery, even though 63 % of resection margins were positive (a free margin was not defined as a tumor-free extent of more than 1 mm), subsequent surgical specimens showed residual carcinoma in only 2.8 % but LNM in 7.6 % 209 .…”
Section: Management After Endoscopic Resectionmentioning
confidence: 99%
“…In a recent study evaluating risk factors for an adverse prognosis after ER of T1 tumors, the variables related to surgical rescue were piecemeal resection (OR 4.48, 95 %CI 1. 48 [208]. So, clearly a positive vertical margin is a risk factor for residual disease and need for additional surgery and potential for LNM, as suggested by the study of Boenicke et al This showed that in patients who underwent ER of malignant polyps followed by surgery, even though 63 % of resection margins were positive (a free margin was not defined as a tumor-free extent of more than 1 mm), subsequent surgical specimens showed residual carcinoma in only 2.8 % but LNM in 7.6 % [209].…”
Section: Colorectal Lesionsmentioning
confidence: 99%
“…These images were annotated by a team of experienced endoscopists (JC, JH, MP, DR, LR, and ES) with the locations of the polyps (bounding boxes). All the endoscopists participated in the Galician CRC screening program [67]. The median number of colonoscopies performed annually by the endoscopists enrolled in the screening program (71 from 7 hospitals) was 278 (IQR 56-507) and the median adenoma detection rate was 65.3% (IQR 60.0-70.1%).…”
Section: Image Datasetmentioning
confidence: 99%
“…Galician CRC mass screening and its implementation have been described elsewhere [13]. The CRC screening program includes the central coordination and management of patient follow-up after polyp resection depending on their risk according to EU guidelines for quality assurance on CRC screening recommendations [14].…”
Section: Description Of the Galician Crc Screening Programmentioning
confidence: 99%